Friction and Wear Properties of Phosphonium Based Ionic Liquid Used as Additive in Synthetic and Bio Based Lubricants - Nouman Haider; Muhammad Moneeb Butt; Rehan Zahid; Mian Ashfaq Ali; Jawad Aslam; Riaz Ahmed Mufti; Muhammad Usman Bhutta (Tribology in Industry)
This research investigated the tribological performance of phosphonium-based ionic liquid Tri hexyl tetra decyl-phosphonium bis (2, 4, 4-trimethylpentyl) phosphinate (IL) when used as an additive at a concentration of 1wt% to Cotton seed oil (CSO), Rattan Jot oil (RJO), Waste Cooking oil (WCO) and Polyalphaolefin (PAO) at different operating conditions. The results were compared with conventional PAO base oil. The tribological performance of all lubricants was studied using a Vertical Universal Testing Machine (MMW1A) and wear scar diameter were measured using an electronic microscope OLYMPUS DX-1000. The results indicated that the addition of ionic liquid further enhanced the tribological performance in terms of wear for all bio-lubricants except for waste cooking oil. However, the addition of ionic liquid does not have much effect on the tribological performance of PAO. Rattan Jot oil was found to have the best tribological properties with the addition of ionic liquid.